2008
DOI: 10.3892/mmr_00000008
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of vascular hepatocyte growth factor concentration and lipid accumulation between telmisartan and losartan in ApoE-deficient mice

Abstract: Abstract. The favorable metabolic effects of telmisartan have been related to its blockade of angiotensin (Ang) II receptor and action as a partial agonist of peroxisome proliferatoractivated receptor γ (PPARγ). We designed a comparative study of telmisartan and losartan in ApoE-deficient mice. ApoE-deficient mice were fed a high-fat diet with or without telmisartan (10 mg/kg/day) or losartan (30 mg/kg/day) for 3 months. Treatment with telmisartan or losartan significantly reduced blood pressure, but did not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…PPARγ has been reported to bind to the putative peroxisome proliferator response element (PPRE) in the promoter region of the HGF gene, resulting in an increase in HGF gene transcription, mRNA expression and protein secretion (9). Our group of investigators have reported that telmisartan (another PPARγ agonistic ARB), but not losartan (a classical ARB), improved endothelial dysfunction and fatty liver, due to an increased tissue HGF level (16). More directly, using AT1R KO mice, telmisartan, but not losartan, exhibited renal protective effects in a unilateral ureteral obstruction model (10).…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ has been reported to bind to the putative peroxisome proliferator response element (PPRE) in the promoter region of the HGF gene, resulting in an increase in HGF gene transcription, mRNA expression and protein secretion (9). Our group of investigators have reported that telmisartan (another PPARγ agonistic ARB), but not losartan (a classical ARB), improved endothelial dysfunction and fatty liver, due to an increased tissue HGF level (16). More directly, using AT1R KO mice, telmisartan, but not losartan, exhibited renal protective effects in a unilateral ureteral obstruction model (10).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study confirmed that the vascular protective potential of telmisartan against diabetes mellitus‐associated VED and associated vascular complications is predominantly mediated through its partial PPARγ activating property (Toyama et al ., 2011). Telmisartan treatment of apolipoprotein E‐deficient mice fed a high‐fat diet was shown to significantly reduce blood pressure and considerably improve endothelial dysfunction (as assessed by the vasodilator response to acetylcholine) by modulating eNOS expression in the aorta; an effect that might be due to its action as a partial agonist of PPARγ (Nakagami et al ., 2008). Moreover, telmisartan was suggested to enhance the bioavailability and vascular generation of NO through a PPARγ‐mediated action (Ikejima et al ., 2008).…”
Section: Is Submaximal Activation Of Pparγ a Valuable Approach In Thementioning
confidence: 99%
“…Cardiovascular pathology and AS have been observed to be associated with reduced local amounts of HGF in cardiac and vascular cells ( 398 400 ). Several drugs such as ARBs (angiotensin II receptor blockers) ( 400 402 ), ACEIs (angiotensin-converting-enzyme inhibitors) ( 399 , 400 , 403 ) and PPAR-γ agonists ( 404 ) have been shown to upregulated HGF, resulting in suppression of AS ( 402 , 405 ). Interestingly, melatonin has also been shown to upregulate HGF expression both in vitro ( 189 , 190 ) and in vivo ( 407 ).…”
Section: Effects Of Melatonin On Atherosclerotic Plaquementioning
confidence: 99%